Abundance and composition of zooplankton in the straits of Malacca - Rezai, Hamid; Md. Yusoff, Fatimah; Arshad, Aziz; Ross, Othman (Taylor and Francis, 2009)
The zooplankton composition and distribution were studied during four oceanographic cruises in the Straits of Malacca between November 1998 and August 2000 with 140 μm-mesh and 45-cm diameter NORPAC net. Zooplankton samples were analyzed for the faunal composition and abundance. Zooplankton abundance peaked during pre-southwest monsoon (mean of 12, 918 ± 5, 635 ind. m3). Copepods were the most important constituents of the zooplankton in all areas. Copepods (including copepodites) accounted for 71.3%, 71.2%, 70.9% and 57.9% of the total zooplankton populations during consecutive cruises I, II, III and IV, respectively. Molluscs (6.3% to 12.4%) and crustacean's nauplii (4.4% to 6.0%) comprised the important groups of non-copepod zooplankton. Spatio-temporal variation in zooplankton abundance was not statistically significant. Zooplankton was more abundant in the near-coastal areas than in offshore areas, but the difference was not significant.